2018
DOI: 10.3390/genes9030158
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hybrid Sequence-Based Model for Identifying Anticancer Peptides

Abstract: Cancer is a serious health issue worldwide. Traditional treatment methods focus on killing cancer cells by using anticancer drugs or radiation therapy, but the cost of these methods is quite high, and in addition there are side effects. With the discovery of anticancer peptides, great progress has been made in cancer treatment. For the purpose of prompting the application of anticancer peptides in cancer treatment, it is necessary to use computational methods to identify anticancer peptides (ACPs). In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 57 publications
0
61
0
Order By: Relevance
“…The sequence information of proteins should be described precisely in the process of protein representation [ 10 , 11 ]. The study of protein representation has been paid more attention these years, such as the amino acid composition (AAC) model used in [ 12 , 13 , 14 ], g-gap dipeptide composition, proposed in [ 15 ], 400D [ 16 ], 188D [ 17 ], and others. The protein is represented by a simple vector in AAC model, whose elements represent the normalized occurrence frequency of the native amino acid in the peptide chain.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence information of proteins should be described precisely in the process of protein representation [ 10 , 11 ]. The study of protein representation has been paid more attention these years, such as the amino acid composition (AAC) model used in [ 12 , 13 , 14 ], g-gap dipeptide composition, proposed in [ 15 ], 400D [ 16 ], 188D [ 17 ], and others. The protein is represented by a simple vector in AAC model, whose elements represent the normalized occurrence frequency of the native amino acid in the peptide chain.…”
Section: Introductionmentioning
confidence: 99%
“…SVM is a widely used machine learning algorithm (Ding and Li, 2015;Li et al, 2015;Zeng et al, 2017;Ding et al, 2017a;Zhang et al, 2019;Tan et al, 2019a) and was used in this study to identify 6mA sites in the rice genome. SVM is also widely used in bioinformatics fields (Zou et al, 2016b;Wang et al, 2018;Wei et al, 2018;Xiong et al, 2018;Zeng et al, 2018a;Xu et al, 2018a;Xu et al, 2018b;Xu et al, 2018c;Li et al, 2019). Our experiments showed that SVM was more suitable for the purposes of the present study than were the other algorithms.…”
Section: Support Vector Machinementioning
confidence: 73%
“…Feature selection is an effective way to remove redundant information and prevent over-fitting in machine learning modeling (Tang et al, 2017;Xu et al, 2018a;Cheng et al, 2019a;Liu, 2019;Sun et al, 2019;. Several feature selection technologies, including ANOVA (Lv et al, 2019b) and MRMD (Zou et al, 2016), have been developed and are widely used for DNA, RNA, and protein identification (Xu et al, 2018b). In this work, an LGBM (Ke et al, 2017) 1 wrapper was used to select appropriate feature spaces for model training.…”
Section: Feature Selectionmentioning
confidence: 99%